2016
DOI: 10.1161/jaha.116.003767
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Association Between Depressive Symptoms, Coronary Heart Disease, and Stroke in Black and White Adults: The REasons for Geographic And Racial Differences in Stroke (REGARDS) Study

Abstract: BackgroundDepression is a relapsing and remitting disease. Prior studies on the association between depressive symptoms and incident cardiovascular disease (CVD) have been limited by single measurements, and few if any have examined both incident coronary heart disease and stroke in a large biracial national cohort. We aimed to assess whether time‐dependent depressive symptoms conferred increased risk of incident CVD.Methods and ResultsBetween 2003 to 2007, 22 666 black and white participants (aged ≥45 years) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 53 publications
5
26
0
Order By: Relevance
“… 5 40 Although meta-analyses have shown a positive association, majority of the studies included in these meta-analyses did not take into account stroke risk factors such as BMI or alcohol use. 41 The results of this study were consistent with at least one prospective study which found that depression was not associated with stroke risk among older adults, after adequately controlling for covariates. 42 43 Taken together, depression did not appear to be a relevant risk factor of stroke in older adults.…”
Section: Discussionsupporting
confidence: 89%
“… 5 40 Although meta-analyses have shown a positive association, majority of the studies included in these meta-analyses did not take into account stroke risk factors such as BMI or alcohol use. 41 The results of this study were consistent with at least one prospective study which found that depression was not associated with stroke risk among older adults, after adequately controlling for covariates. 42 43 Taken together, depression did not appear to be a relevant risk factor of stroke in older adults.…”
Section: Discussionsupporting
confidence: 89%
“…Despite these less consistent relationships according to sex, scales of anxiety assessment, and assessment time, current findings could be interpreted that increased depressive or anxiety symptoms could occur with higher CV risk estimates and predict higher CV risk estimates in the future. The observation would support previous knowledge about the associations between depressive and anxiety symptoms and CVD and CV risk factors (Batelaan et al, 2016;Castaneda et al, 2016;de Miranda Azevedo et al, 2014;Lopez-Leon et al, 2010;Moise et al, 2016;Rutledge et al, 2009;Salaycik et al, 2007;Scherrer et al, 2003;Shen et al, 2008;Ye et al, 2013).…”
Section: Discussionsupporting
confidence: 87%
“… 1 9 Nonetheless, our previously published study, which excluded those with a history of CVD, similarly found a strong relationship between time-varying depressive symptoms and CVD death. 31 …”
Section: Discussionmentioning
confidence: 99%